À propos de quelques structures lexico-syntaxiques du type dit comparatif dans un texte scientifique - Hajok, Alicja (Neophilologica, 2016)
This article presents several lexical and syntactic structures characteristic of scientific texts. Markers of comparison such as être identique à, différer de, comme are one element of the analysed structures. The proposed analyses treat phraseology in a wider context (phraséologie étendue) and are a part of a broader research on motive.